2018
DOI: 10.11646/zootaxa.4440.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater crab genera Ghatiana Pati &amp; Sharma, Gubernatoriana Bott, <br />and Inglethelphusa Bott (Crustacea: Decapoda: Brachyura: Gecarcinucidae) revisited, with descriptions of a new genus and eleven new species

Abstract: The taxonomy of three morphologically related and endemic genera of the northern Western Ghats (Ghatiana Pati & Sharma, 2014, Gubernatoriana Bott, 1970, and Inglethelphusa Bott, 1970) is re-assessed to accommodate several new taxa. We describe a new genus, Sahyadriana gen. nov. and its five new species [S. billyarjani sp. nov., S. pachyphallus sp. nov., S. sahyadriensis sp. nov. (type species), S. tenuiphallus sp. nov., and S. woodmasoni sp. nov.]. Additionally, three new species each of Ghatiana (Gh. bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…It was recorded from the Western Ghats at the Bannerghatta National Park of Bangalore Urban district, Bandipur Tiger Reserve of Chamarajanagar district, and Hosur of Uttara Kannada district (see Srivastava, 2007;2013;Pati and Sharma, 2014). The species, however, was never included in the Western Ghats fauna (see Pati and Thackeray, 2018). The present specimens of O. wagrakarowensis from Wayanad district of Kerala, therefore, constitute the first reliable report of the species from the Western Ghats.…”
Section: New Records Of Freshwater Crabs From Keralamentioning
confidence: 76%
See 2 more Smart Citations
“…It was recorded from the Western Ghats at the Bannerghatta National Park of Bangalore Urban district, Bandipur Tiger Reserve of Chamarajanagar district, and Hosur of Uttara Kannada district (see Srivastava, 2007;2013;Pati and Sharma, 2014). The species, however, was never included in the Western Ghats fauna (see Pati and Thackeray, 2018). The present specimens of O. wagrakarowensis from Wayanad district of Kerala, therefore, constitute the first reliable report of the species from the Western Ghats.…”
Section: New Records Of Freshwater Crabs From Keralamentioning
confidence: 76%
“…With the addition of these two new records, Kerala has 37 species of gecarcinucid crabs, including four species of Oziotelphusa Müller, 1887 and six species of Vanni Bahir and Yeo, 2007. The Western Ghats of India is now known to have 59 freshwater crab species in 18 genera (Pati and Thackeray, 2018).…”
Section: New Records Of Freshwater Crabs From Keralamentioning
confidence: 99%
See 1 more Smart Citation
“…Till date, this species has been reported from Assam, Nagaland, Arunachal Pradesh, Meghalaya, Mizoram, and West Bengal (Mitra 2017;Pati and Thackeray 2018) (Fig. 4).…”
Section: Distributionmentioning
confidence: 98%
“…Similarly, in southern parts of India Barytelphusa cunicularis is a common freshwater crab and its distribution extends from Himachal Pradesh in the North to Kerala in the South (Pati and Sharma 2014). In India, 120 species of freshwater crabs have been reported from different geographical regions and among these 38 species are reported from North East India (Pati and Thackeray, 2018). The IUCN red data list revealed that most of these crabs of North East India are in data deficient condition and some of them are 'least concern' in the context of conservation scale (Cumberlidge et al 2009) where reportedly Liotelphusa quadratic and Phricotelphusa elegans are in vulnerable condition and Maydelliathelphusa falcidigitis, Liotelphusa gageii, and Liotelphusa laevis are considered as near threatened (Mitra 2017).…”
Section: Introductionmentioning
confidence: 99%